FIXEL: Mobile application for roadside assistance provider decision making using TOPSIS / Mohd Suffian Sulaiman ... [et al.] - Sulaiman, Mohd Suffian; Azmi, Mohd Fitri Afiq; Derasit, Zuraidah; Azmi, Azri (UiTM Cawangan Perlis, 2024)
Many drivers have faced the struggle of getting help when their vehicle breaks down on the road. This difficult situation is extremely stressful because there are limitations to seeking help, such as the service provider being too far away or the service provider's contact number being unavailable. The complication of deciding to choose a service provider is also occurring because of the eagerness to fulfil different kinds of aspects, such as the lowest price of the services and the shortest distance from the service provider. From the service provider’s perspective, it has become a challenge to get new customers when they are unfamiliar with their surroundings. Usually, the drivers will choose the most popular service provider, which may be far away from them. These issues sparked the motivation for this study, which aims to assist drivers and service providers through the mobile platform. One of the multi-criteria decision-making methods was employed to enhance the quality of choosing the right service provider based on the criteria involved, which are service availability, prices, distances and ratings. The result of this study would benefit drivers and service providers by improving decision-making, enhancing the customer experience, optimizing resource utilization and reducing cost.